Knowledge, Attitudes, and Iron Intake among Adolescent Girls: A Cross-Sectional Study at SMAN 1 Cirebon City - Sri Ayu Lestari; M.Duddy Satrianugraha Wahidin; Doddy Rizqi Nugraha (Indonesian Journal Publisher, 2026)
This study aimed to determine the relationship between knowledge and attitudes regarding iron deficiency anemia and iron intake among adolescent girls at State Senior High School 1 Cirebon City. This quantitative analytical observational study employed a cross-sectional design involving 114 female students selected using purposive sampling. Knowledge and attitudes were assessed using structured questionnaires, while iron intake was measured using a 1×24-hour food recall. Data were analyzed using ordinal logistic regression. The results showed that knowledge was significantly associated with iron intake (β = 0.896; 95% CI: 0.064–1.727; p = 0.035), indicating that higher knowledge was associated with better iron intake. Attitude was also significantly associated with iron intake (β = 2.354; 95% CI: 0.075–4.633; p = 0.043), suggesting that a more positive attitude was associated with better iron intake. The model explained 36.6% of the variation in iron intake (Nagelkerke R² = 0.366). In conclusion, knowledge and attitudes regarding iron deficiency anemia were significantly associated with iron intake among adolescent girls, indicating the importance of strengthening nutrition education and promoting positive attitudes to improve iron intake and support anemia prevention programs